Nano Copper in Poultry Nutrition: Potential Effect and Future Prospect - A Review: - Noor, Aminulla; T M, Prabhu; B N, Suresh; A. Mostamand (Indian Journal of Animal Nutrition, 2023)
Copper (Cu) is an essential trace element and plays a key role in maintenance, production and health of birds. Hence, supplementation of Cu has become a common practice in poultry diets. However, the bioavailability of Cu from feed ingredients as well as from its inorganic salts is low. This results in Cu deficiency in the body or may lead to excess excretion and environmental toxicity if supplemented at higher levels. Thus, strategies to improve bioavailability of Cu from its conventional sources for use in poultry diets assume significance. In this context, nano-technology has been demonstrated to be beneficial in various biological fields including poultry nutrition. Nano Cu (NCu) has additional novel properties (size, shape, concentration, surface charge and reactivity) compared to its conventional inorganic form. The improved nutrients utilization and growth performance of birds was observed upon dietary inclusion of NCu. This effect was attributed to better gut health due to antimicrobial properties of NCu and also due to its positive effect on growth hormone axis, expression of hypothalamic appetite regulating genes and dietary energy and fat utilization. In various studies, the metabolizability of nutrients and growth performance of birds was improved or remained comparable at reduced supplementation level of NCu in the diets. Further, reduced Cu interaction with phytic acid, iron and zinc forming an insoluble complex was observed when NCu used in the diets. Increased Cu deposition in the tissues and reduced Cu excretion due to NCu inclusion in the poultry diets were also observed. However, suppressed immune response and antioxidant status was reported due to relatively higher dose of dietary NCu in chicken. This may be due to inappropriate stimulation of immune system or over production of reactive oxygen species due to nanoparticles in the body. Due to numerous advantages, the application of NCu in poultry nutrition is continue to develop and further studies are required to fulfil the knowledge gap in physicochemical characteristics of nanoparticles and their potential effect on various parameters in poultry.